Adoptive transfer of helminth antigen‐pulsed dendritic cells protects against the development of experimental colitis in mice. Issue 11 (25th September 2015) - Matisz, Chelsea E.; Leung, Gabriella; Reyes, Jose Luis; Wang, Arthur; Sharkey, Keith A.; McKay, Derek M.
Abstract : Infection with helminth parasites and treatment with worm extracts can suppress inflammatory disease, including colitis. Postulating that dendritic cells (DCs) participated in the suppression of inflammation and seeking to move beyond the use of helminths per se, we tested the ability of Hymenolepis diminuta antigen‐pulsed DCs to suppress colitis as a novel cell‐based immunotherapy. Bone marrow derived DCs pulsed with H. diminuta antigen (HD‐DCs), or PBS‐, BSA‐, or LPS‐DCs as controls, were transferred into wild‐type (WT), interleukin‐10 (IL‐10) knock‐out (KO), and RAG‐1 KO mice, and the impact on dinitrobenzene sulphonic acid (DNBS)‐induced colitis and splenic cytokine production assessed 72 h later. Mice receiving HD‐DCs were significantly protected from DNBS‐induced colitis and of the experimental groups only these mice displayed increased Th2 cytokines and IL‐10 production. Adoptive transfer of HD‐DCs protected neither RAG‐1 nor IL‐10 KO mice from DNBS‐colitis. Furthermore, the transfer of CD4 + splenocytes from recipients of HD‐DCs protected naïve mice against DNBS‐colitis, in an IL‐10 dependent manner. Thus, HD‐DCs are a novel anti‐colitic immunotherapy that can educate anti‐colitic CD4 + T cells: mechanistically, the anti‐colitic effect of HD‐DCs requires that the host has an adaptive immune response and the ability to mobilize IL‐10.